1997
DOI: 10.1172/jci119587
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous stimulation of slow-wave sleep and growth hormone secretion by gamma-hydroxybutyrate in normal young Men.

Abstract: The aim of this study was to investigate, in normal young men, whether gamma-hydroxybutyrate (GHB), a reliable stimulant of slow-wave (SW) sleep in normal subjects, would simultaneously enhance sleep related growth hormone (GH) secretion. Eight healthy young men participated each in four experiments involving bedtime oral administration of placebo, 2.5, 3.0, and 3.5 g of GHB. Polygraphic sleep recordings were performed every night, and blood samples were obtained at 15-min intervals from 2000 to 0800. GHB effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
117
2
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(130 citation statements)
references
References 56 publications
7
117
2
4
Order By: Relevance
“…The increases published here for this small GHB dose are around 15 % of that seen from a 0.15 U/kg subcutaneous dose of somatropin (29). Given that the work of Van Cauter suggests 16 that larger doses will be capable of producing an even greater response, the potential for GHB abuse in sport is noteworthy (25). Though current research in this area is limited, the long term administration of GHB to alcoholics did not affect muscle mass or waist to hip ratio, but this may be a consequence of the GH release associated with GHB administration being suppressed in alcoholics (30).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The increases published here for this small GHB dose are around 15 % of that seen from a 0.15 U/kg subcutaneous dose of somatropin (29). Given that the work of Van Cauter suggests 16 that larger doses will be capable of producing an even greater response, the potential for GHB abuse in sport is noteworthy (25). Though current research in this area is limited, the long term administration of GHB to alcoholics did not affect muscle mass or waist to hip ratio, but this may be a consequence of the GH release associated with GHB administration being suppressed in alcoholics (30).…”
Section: Discussionmentioning
confidence: 56%
“…These doses are equivalent to approximately 35 mg/kg, 42 mg/kg and 50 mg/kg respectively, and therefore are all in excess of the dose administered in this study (25).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Why does this occur? It has been well documented that GHB can stimulate growth hormone and ACTH and cortisol release, which will induce resistance to the action of insulin [3]. It has also been shown that recreational use of GHB, presumably in high doses, can result in pseudoCushing's syndrome [4].…”
mentioning
confidence: 99%